Lathe Training Process at the Regional Technical Implementation Unit (UPTD) of Karawang Vocational Training Center (BLK) - Awaludin, Awaludin; Meilya, Ika Rizqi; Syahid, Ahmad (Universitas Negeri Padang, 2025)
The main problem studied in this research is the lathe machine training process, because this research wants to get various facts about the lathe machine training process at the UPTD Job Training Center (BLK), both in terms of objectives, processes, training methods, skills, evaluation and training results, The author chose to use a qualitative research method so that the research could be more precisely directed according to the research objective, namely finding out how the lathe machine training process is at the UPTD Vocational Training Center (BLK) Karawang, so that this research is more appropriate using qualitative research using the case study method which was carried out with clear facts. Obtained in the field. The results of this research are (1) the lathe machine training process equips the trainees with practical skills in operating a lathe machine, so that they are able to do the work more efficiently and accurately (2) the skills of the trainees after attending lathe machine training at the UPTD Job Training Center (BLK ) Karawang has succeeded in increasing knowledge of how to operate a lathe machine safely and efficiently, lathe machine training participants can also increase the specified dimensions and tolerances, set the machine correctly, including speed and cutting depth, understand safety procedures when operating the machine which also shows their understanding of the risks involved.